Asbestos Litigation - Carroll, Stephen J. (RAND Corporation, 2005)
Asbestos litigation is the longest-running mass tort litigation in U.S. history. Through 2002, approximately 730,000 individuals have brought claims against some 8,400 business entities, and defendants and insurers have spent a total of $70 billion on litigation. Building on previous RAND briefings, the authors report on what happened to those who have claimed injury from asbestos, what happened to the defendants in those cases, and how lawyers and judges have managed the cases.